A novel role of the antidepressant paroxetine in inhibiting neuronal Kv7/M channels to enhance neuronal excitability - Huan Shi; Qinqin Li; Fang Hu; Yani Liu; KeWei Wang (Translational Psychiatry)
Abstract The voltage-gated Kv7/KCNQ/M potassium channels exert inhibitory control over neuronal membrane excitability. The reduction of Kv7 channel function can improve neuronal excitability that defines the fundamental mechanism of learning and memory. This suggests that pharmacological inhibition of Kv7 channels may present a therapeutic strategy for cognitive improvement. Paroxetine, a selective serotonin reuptake inhibitor, is widely used in the treatment of various types of depression with reported improvements in memory and attention. However, the exact mechanism underlying cognitive improvement by paroxetine remains poorly understood. In this study, we demonstrate that paroxetine inhibits whole-cell Kv7.2/Kv7.3 channel currents in a concentration-dependent manner with an IC50 of 3.6 ± 0.2 μΜ. In single-channel recording assay, paroxetine significantly reduces the open probability of Kv7.2/Kv7.3 channels. Moreover, paroxetine exhibits an inhibition of the native M-current and an increase in the firing of action potentials in hippocampal neurons. Taken together, our findings unveil a novel role of the antidepressant paroxetine in inhibiting M-current, providing insights into its pharmacological effects on cognition enhancement.